Suicide Ideas as Dissociative Symptoms in Patients with Severe Depression: A Case report - Makka, Isna Meirilla Zahara Al; Yusmadewi, Aaliyah; Fatwa, Ahmad Misbahul Ulum; Billah, Illa; Imron, Muhammad Istio Hadi Al; Suwarti, Ariyani Sri; Algristian, Hafid (Psychosocia : Journal of Applied Psychology and Social Psychology, 2025)
Dissociative symptoms such as depersonalization, derealization, and amnesia frequently occur in patients with severe depression and significantly heighten suicide risk, particularly when childhood trauma is present. This case report presents a 20-year-old woman with major depressive disorder and dissociative symptoms including unintentional self-harm, hallucinations, and nightmares related to past abuse. Clinical data were collected via structured clinical interviews, direct observation, and patient self-report, with diagnostic confirmation using DSM-5 criteria. The case illustrates how dissociation, trauma, and disrupted emotional regulation interact to intensify hopelessness and impulsivity. Comprehensive treatment, including trauma-focused cognitive behavioral therapy (CBT), pharmacotherapy, and emotional expression techniques such as journaling, led to gradual symptom relief. This case highlights the importance of early identification of dissociative symptoms in depressed individuals with trauma history to reduce suicide risk.